Self-Esteem and Defense Mechanisms in Infertile Couples Based on the Cause of Infertility in Royan Infertility Treatment Center in 2017 - farideh malekzadeh; behnaz navid; Maryam Mohammadi; Reza Omani-Samani (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2020)
Introduction: Infertility could decrease the self-esteem of the infertile couples. Using the defensive style is one way to deal with stressful events. Therefore, the aim of this study was to investigate the role of self-esteem and defense mechanisms based on the cause of infertility. Methods: In this cross-sectional study, 400 infertile couples referred to infertility center in Tehran, Iran. Participates classified in 4 groups for the cause of infertility: female, male, both and unknown. Data gathering tools in this study were demographic questionnaire, Rosenberg Self-Esteem Scale and Defense Styles Questionnaire (DSQ). Data were analyzed (SPSS 18 software) using paired t-test for comparison between the groups according to the cause of infertility and using regression analyses tests. Results: The results of this study showed that men in female infertility group has significantly higher self –esteem than other groups (P<0.049). In couples, husbands with female and male factor showed more self-esteem than their wives (P< 0.001, P<0.008, respectively). In defense mechanisms, there was no difference between women, men, and couples. In this study, self-esteem showed a negative relationship with immature and neurotic defense mechanisms and a positive relationship with mature defense mechanism. Conclusion: The findings of this study showed that women had higher levels of vulnerability than their husbands did even when they were not the cause of infertility so they have a low self-esteem. Therefore, it is suggested that infertile women receive more psychological counseling than men, and in order to facilitate the treatment of infertile couples and provide better services to improve marital relationships and solve their problems, differences between men and women about psychological issues should be considered.